Meningkatkan Mutu Lembaga Pendidikan Islam Berbasis Manajemen Pembiayaan - Hidayat Hidayat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In this research the author tries to highlight the factors that influence the thinking model of the Islamic education system. For the author, the central issues are management, finance, quality and education. Apart from that, in this research the author used qualitative research methods. These approaches are described in more detail and classified according to research conditions. Apart from that, the author also uses library research methods. The results of this research show that: Educational financial management influences the quality of general education. The results of this research show that fund management is a process of optimizing existing funding sources, allocating existing funds and allocating them in the form of facilities and infrastructure to support the learning process in order to create a learning process that is much more effective, efficient and better. To achieve quality learning, education costs must be managed optimally and optimally. Therefore, educational financial management steps must be considered and made a top priority.